2020
DOI: 10.21894/jopr.2020.0082
|View full text |Cite
|
Sign up to set email alerts
|

Palm Tocotrienols Cause Cleavage of Poly-(Adp)-Ribose Polymerase Enzyme and Down-Regulation of Cyclooxygenase-2 Protein Level in Human Breast Cancer Cells

Abstract: Breast cancer is a leading cause of cancer-related deaths in women globally. The anti-cancer effects of various forms of vitamin E from palm oil [tocotrienol-rich fraction (TRF): natural form of vitamin E complex in palm oil, tocotrienol-enriched fraction (TEF), and major vitamin E homologues in palm oil: a-tocopherol (aToc) and tocotrienols (T3) (a, d or g)] were tested on two human breast cancer cell lines [MDA-MB-231 (triple negative) and MCF-7 (oestrogen-dependent)]. Chronic inflammation plays a key role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Thus, our data demonstrate that PO (particularly at higher concentrations) has the potential ability to restrain the proliferation of chronic myeloid leukaemia. This observation is consistent with previous in vitro and in vivo studies, which demonstrate that PO and its derived product have a significant role against cancer cells (Absalome et al, 2020;Loganathan et al, 2021;Sambanthamurthi et al, 2011). The underlying process of cell death caused by PO has been evaluated by some researchers.…”
Section: Growth Rates Of K562 Cells In the Presence Of Po Or/and Pbmsupporting
confidence: 92%
“…Thus, our data demonstrate that PO (particularly at higher concentrations) has the potential ability to restrain the proliferation of chronic myeloid leukaemia. This observation is consistent with previous in vitro and in vivo studies, which demonstrate that PO and its derived product have a significant role against cancer cells (Absalome et al, 2020;Loganathan et al, 2021;Sambanthamurthi et al, 2011). The underlying process of cell death caused by PO has been evaluated by some researchers.…”
Section: Growth Rates Of K562 Cells In the Presence Of Po Or/and Pbmsupporting
confidence: 92%
“…On the palm phytonutrient research front, several studies were published on the mechanisms of action by tocotrienols in inhibiting breast cancer cell growth both in vitro and in vivo. Loganathan et al (2021) reported that tocotrienols have exhibited anti-proliferative effects on human breast cancer cells by promoting programmed cell death or apoptosis possibly through the inactivation and down-regulation of two significant markers: poly-(ADP)-ribose polymerase-1 (PARP-1) and cyclooxygenase-2 (COX-2). In a breast cancer mice model, gamma-tocotrienol supplementation suppresses the growth of breast cancer tumour, as well as metastasis (Subramaniam et al, 2021a).…”
Section: P R E S Smentioning
confidence: 99%
“…Tocotrienols are established as natural bioactive compounds with the ability to reduce cancer risk (Aggarwal et al, 2019). The latest findings by Loganathan et al (2020d) portrayed the functionality of palm tocotrienols to exert anti-proliferative and proapoptotic effects based on the manifestation of poly-(adenosine diphosphate)-ribose polymerase (PARP-1) cleavage and cyclooxygenase-2 (COX-2) inactivation of human breast cancer cells. A systematic review on the safety and neuroprotective efficacy of palm oil and tocotrienols-rich fractions (TRF) by Ismail et al (2020a) inferred that the role of palm TRF or alpha-tocotrienol (α-T3) stimulates the cognitive performance of healthy animal and cognitive functions.…”
Section: P R E S Smentioning
confidence: 99%